2021
DOI: 10.1111/1541-4337.12873
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the properties and functionalities of biodegradable and semibiodegradable food packaging materials

Abstract: The development of biodegradable food packaging with superior properties and functionalities compared to conventional food packaging is one of the emerging research interests. Immediate disposal of conventional single use nonbiodegradable food packaging results in adverse environmental impact. Utilization of either biomass‐based, microorganism‐derived, or biotechnologically synthesized biopolymers as biodegradable matrices is the common approach toward achieving sustainability. Consequently, starch and cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 150 publications
(231 reference statements)
0
13
0
Order By: Relevance
“…Starch foam biodegrades rapidly, but foams made with modified starch or composite foam (added with agroindustrial residues) have longer degradation time. 74 For the EPS foam tray, there was no significant difference in mass along the study (result not shown) as can be observed in Figure 6A. EPS is a known non-biodegradable plastic material that is difficult to decompose in the environment.…”
Section: Foam Tray Biodegradabilitymentioning
confidence: 78%
“…Starch foam biodegrades rapidly, but foams made with modified starch or composite foam (added with agroindustrial residues) have longer degradation time. 74 For the EPS foam tray, there was no significant difference in mass along the study (result not shown) as can be observed in Figure 6A. EPS is a known non-biodegradable plastic material that is difficult to decompose in the environment.…”
Section: Foam Tray Biodegradabilitymentioning
confidence: 78%
“…The best layer in which to use nanofiber is not yet unanimously agreed upon among researchers and is frequently applied in the external layers [ 22 ] or the middle layer [ 50 ]. Thus, by adding a nanofiber to the multilayer design, it is possible to obtain a final product with improved mechanical and barrier properties and the excellent encapsulation capacity of the bioactive compounds [ 90 , 91 ]. According to Monção et al [ 92 ], in the last 10 years, new active food packaging development has increased, with a considerable number referring to multilayer systems.…”
Section: Multilayer Systems As Active Biodegradable Food Packagingmentioning
confidence: 99%
“…Alternative, non-edible sources of starch are worthwhile to investigate for the biodegradable food packaging sector to minimise food security concerns. Application of agro-industrial waste as alternative biodegradable food packaging matrices would ensure better food security, assure eco-friendliness and help achieving economic benefits through their valorisation [ 24 ]. Cassava (Manihot esculenta) bagasse or cassava pulp is a cassava industrial waste and has been reported to be an excellent source of residual starch and fibre [ 25 ].…”
Section: Introductionmentioning
confidence: 99%